Preservation of health in Islamic law - Deuraseh, Nurdeng (IIUM Press, 2009)
Preservation of health (hifz al-sihhah) is the most important branch of Islamic medicine since it is primarily concerned with the prevention of illness rather than cure. This book represents as of the few attempts to introduce the role of Islamic medicine, although Chapter One provides information about a historical background of the preservation of health in Islam, but its aim is to provide a fresh and timely overview of major aspects of legal, ritual and spiritual structures of the Islamic laws, foods and drinks as well as environmental laws, for maintaining and preserving human health. Findings indicated that prevention of any diseases from Islamic medical law perspectives cannot attain any real success unless it emanates from Islamic fundamental teaching, namely: the pillars of Islam. Iman and observance of the Islamic rituals such as Salah, zakah, sawm and hajj, have played an important role in shaping the model personality of the Muslim, in boosting the spiritual motivation for attitude change, and in disseminating the message of prevention. This indicates that bodily and spiritual health goes hand in hand and that psycho-spiritual balance and health is primary while physical health is a secondary one.